Antigen Display, T-Cell Activation, and Immune Evasion during Acute and Chronic Ehrlichiosis - Nandi, Bisweswar (American Society for Microbiology (ASM), 2009)
How spatial and temporal changes in major histocompatibility complex/peptide antigen presentation to CD4 T cells regulate CD4 T-cell responses during intracellular bacterial infections is relatively unexplored. We have shown that immunization with an ehrlichial outer membrane protein, OMP-19, protects mice against fatal ehrlichial challenge infection, and we identified a CD4 T-cell epitope (IA(b)/OMP-19(107-122)) that elicited CD4 T cells following either immunization or infection. Here, we have used an IA(b)/OMP-19(107-122)-specific T-cell line to monitor antigen display ex vivo during acute and chronic infection with Ehrlichia muris, a bacterium that establishes persistent infection in C57BL/6 mice. The display of IA(b)/OMP-19(107-122) by host antigen-presenting cells was detected by measuring intracellular gamma interferon (IFN-γ) production by the T-cell line. After intravenous infection, antigen presentation was detected in the spleen, peritoneal exudate cells, and lymph nodes, although the kinetics of antigen display differed among the tissues. Antigen presentation and bacterial colonization were closely linked in each anatomical location, and there was a direct relationship between antigen display and CD4 T-cell effector function. Spleen and lymph node dendritic cells (DCs) were efficient presenters of IA(b)/OMP-19(107-122), demonstrating that DCs play an important role in ehrlichial infection and immunity. Chronic infection and antigen presentation occurred within the peritoneal cavity, even in the presence of highly activated CD4 T cells. These data indicated that the ehrlichiae maintain chronic infection not by inhibiting antigen presentation or T-cell activation but, in part, by avoiding signals mediated by activated T cells.